2015
DOI: 10.1093/annonc/mdv355
|View full text |Cite
|
Sign up to set email alerts
|

Central adiposity, obesity during early adulthood, and pancreatic cancer mortality in a pooled analysis of cohort studies

Abstract: Our results support an association between pancreatic cancer mortality and central obesity, independent of BMI, and also suggest that being overweight or obese during early adulthood may be important in influencing pancreatic cancer mortality risk later in life.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
88
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 134 publications
(94 citation statements)
references
References 59 publications
5
88
1
Order By: Relevance
“…15,16 Specifically, both central adiposity and an increased BMI, which is the most commonly used measure of obesity, are independently associated with PDAC-associated mortality. 17 One recent study also suggested that obesity is associated with worse survival following pancreaticoduodenectomy for PDAC. 15 One concern with utilizing BMI measurements as the sole measure of obesity is that it does not distinguish between visceral and subcutaneous fat.…”
Section: Discussionmentioning
confidence: 99%
“…15,16 Specifically, both central adiposity and an increased BMI, which is the most commonly used measure of obesity, are independently associated with PDAC-associated mortality. 17 One recent study also suggested that obesity is associated with worse survival following pancreaticoduodenectomy for PDAC. 15 One concern with utilizing BMI measurements as the sole measure of obesity is that it does not distinguish between visceral and subcutaneous fat.…”
Section: Discussionmentioning
confidence: 99%
“…21,22 However, BMI is a limited measurement as it does not provide information on fat distribution, which is of importance as many of the complications associated with obesity have been shown to be closely related to abdominal obesity. 23,24 A recent pooled analysis of 20 prospective studies found that waist circumference is a risk factor for MM mortality and that BMI in early adulthood plays an important role later in life regarding MM mortality, particularly in women. 25 In addition, a recent cross-sectional study (n 5 72) found that patients recently diagnosed with MM had higher abdominal fat compared with patients with MGUS, indicating that this parameter might serve as a biomarker for progression from MGUS to MM.…”
Section: Introductionmentioning
confidence: 99%
“…Diabetes, obesity, and smoking are known risk factors for PDA (35). Large epidemiologic analyses have shown obesity is associated with higher risk of PDA in nonsmokers, however this association is weaker or absent in current smokers (46), suggesting obesity-related mechanisms may be of greater importance in the etiology of PDA in nonsmokers.…”
Section: Introductionmentioning
confidence: 99%